(untitled) (Journal of Pharma Insights and Research, 2024)
Pancreatitis is an inflammatory condition of the pancreas, with acute pancreatitis being the most prevalent form. The primary etiologies are gallstones and excessive alcohol consumption, accounting for 70-80% of cases. While most acute pancreatitis cases are mild and self-limiting, approximately 20-30% progress to a severe form characterized by pancreatic necrosis and organ failure, leading to a high mortality rate of around 15%. Chronic pancreatitis is a progressive, debilitating condition resulting from repeated inflammatory episodes or other factors, causing irreversible pancreatic damage and impaired exocrine and endocrine function. Accurate diagnosis and timely intervention are crucial in pancreatitis management. Mild acute pancreatitis is typically managed with supportive care, including fluid resuscitation, pain control, and early enteral nutrition. Severe cases may require intensive care, antibiotic prophylaxis, and interventions for complications like infected necrosis. Chronic pancreatitis necessitates lifestyle modifications, pain management, enzyme supplementation, and potential endoscopic or surgical interventions for duct decompression or resection. This review aims to provide a comprehensive overview of pancreatitis, encompassing its epidemiology, etiology, classification systems, and evidence-based management strategies. Recent advances in diagnostic modalities, novel therapeutic approaches, and surgical techniques are discussed. Additionally, the review highlights the importance of a multidisciplinary approach and the need for tailored treatment plans based on individual patient factors and disease severity